2010
DOI: 10.1007/s10661-010-1570-9
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved and particulate metals in water from Sonora Coast: a pristine zone of Gulf of California

Abstract: The purpose of this study was to investigate the distribution of metals (Cd, Pb, Hg, Cu, Fe, Mn, and Zn) in dissolved and particulate fractions in seawater from Bacochibampo Bay, Northern part of Mexico. Water samples were collected from November 2004 to October 2005. Metal analysis was done by graphite furnace atomic absorption spectroscopy. Results indicated highest concentrations of dissolved Cd and Zn in the sites localized at the mouth and center of the bay. During summer and spring, the highest levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…In comparison to Cr and Ni, the particulate forms of copper and lead at most of the sites dominate over the dissolved phase. This is in accordance with their tendency to show affinity towards solid phase (Garcia-Rico et al, 2011). Partition coefficients for the partitioning of metals between dissolved and particulate forms were calculated (Table 5).…”
Section: Particulate Phasesupporting
confidence: 77%
“…In comparison to Cr and Ni, the particulate forms of copper and lead at most of the sites dominate over the dissolved phase. This is in accordance with their tendency to show affinity towards solid phase (Garcia-Rico et al, 2011). Partition coefficients for the partitioning of metals between dissolved and particulate forms were calculated (Table 5).…”
Section: Particulate Phasesupporting
confidence: 77%
“…The sediments herein have abundant concentrations of metal sulfites [25]. The GC is also characterized by the presence of mining complexes and other industrial and urban activities along the coast, responsible for releasing high amounts of metals into this ecosystem (especially Cd, Cu, Fe, Pb and Zn) [24,26]. García-Rico et al [26] found high levels of Cd, The semi-enclosed Gulf of California (GC) is a marginal sea on the Pacific coast of Mexico and encompasses one of the world's five most productive and diverse ecosystems, being an important feeding ground for a wide variety of marine organisms [20,21].…”
Section: Samplingmentioning
confidence: 99%
“…The GC is also characterized by the presence of mining complexes and other industrial and urban activities along the coast, responsible for releasing high amounts of metals into this ecosystem (especially Cd, Cu, Fe, Pb and Zn) [24,26]. García-Rico et al [26] found high levels of Cd, The semi-enclosed Gulf of California (GC) is a marginal sea on the Pacific coast of Mexico and encompasses one of the world's five most productive and diverse ecosystems, being an important feeding ground for a wide variety of marine organisms [20,21]. The Guaymas Basin, in the GC, is characterized by the presence of a hydrothermal vent that has an organic-rich sedimentary cover enriched in Mn provided by the Colorado River runoff [22,23].…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations